A factor augmentation formulation of the value of international trade - Daniel M. Bernhofen; John C. Brown (Center for Economic Studies and ifo Institute (CESifo), 2012)
We propose a normative assessment of the value of international trade that is rooted in production theory and embeds Ricardo's 1817 formulation of the gains from trade into a multi-factor general equilibrium framework. Without imposing strong assumptions on consumer rationality or data from the economy's autarky equilibrium, our formulation reveals information about both the magnitude and the sources of the gains from trade. A high quality data set on product and task-specific factor employments in 19th-century Japan permits us to apply this approach to answer the following counterfactual: What factor augmentation would have been necessary to compensate the economy for an overnight suspension of trade in its early trade years of 1865-1876? Over the entire period, we find that trade was revealed to be equivalent to a 5.5% increase in Japan's female labour force, a 3.3% increase in its male labour force and a 3.9% increase in its arable land. Efficiency losses associated with a counterfactual suspension of trade averaged between 6.3 and 7.7 percent of the economy's productive capacity.
Keywords: F11; F14; N10; N75; 330; gains from trade; factor augmentation equivalent to trade; natural experiment of Japan; Außenhandelsgewinn; Außenwirtschaft; Faktorenanalyse; Schätzung; Außenhandelsgeschichte; Japan